Significant Others in Substance Abusers' Change Talk During Motivational Interviewing Sessions in the Finnish Probation Service - Sarpavaara Harri (Nordic Studies on Alcohol and Drugs, 2015)
AIMS - This article explores the meanings substance-abusing clients attach to family and friendships during motivational interviewing (MI) sessions in Probation Service. DATA - The analyses are based on videotaped and transcribed data consisting of 82 MI sessions. This database involves the first two counseling sessions of 41 client-counselor pairs. Sessions were videotaped in 12 Probation Service offices in Finland between 2007 and 2009. METHODS - The analysis relies on coding of client's change talk utterances and qualitative semiotic framework. RESULTS - The meanings of the significant others were diverse from the point of view of the client's motivation: family appeared as a support for change, an aspiration, a sufferer, or an obstacle to change; and friendship appeared as an obstacle to change, a surmounted obstacle, a cause to change, or a support to change. CONCLUSIONS - Significant others and their quality are important and diverse factors that promote or hinder change in substance abuser' change talk. Thus, it is suggested that the meaning of significant others should not be overlooked in MI and other substance abuse treatment.